Perceived self-efficacy level and ICTs preference of fishermen for flood risks advisory services in Terrenganu state, Malaysia - Muktar, Bashir Garba; Man, Norsida; Kamarulzaman, Nitty Hirawaty; Makinta, Umar; Umar, Muhammad Gazali (University Community Transformation Centre, Universiti Putra Malaysia, 2017)
The effect of climate change is known to undermine livelihoods especially the agricultural based livelihoods along the coasts regions of nations. Weather extreme events like flood, draught, tsunamis and earthquakes are the resultant effect of climate change. ICTs are utilized in the process of monitoring, mitigation and risk reduction of these weather related extreme events. In Malaysia where the ICTs are ubiquitous and with an impressive access across the population, the flood risks reduction exercise is heavily bridged upon ICTs. The effect of this ICTs mediated advisory service to the fishermen psychological state like level of self-efficacy and motivation to be prepared to flood events is however scarcely researched. The research therefore looked at the psychological effect of climate change, weather and flood risks communication on self-efficacy of fishermen in Setiu, Besut, Kuala Utara and Merang fishing districts of Terengganu state, Malaysia. A random selection of four districts was made out of the seven listed fishing districts in the state. 125 respondents were randomly selected across the selected fishing districts. They were administered questionnaires. Data obtained was analysed using descriptive statistics of frequencies and percentages. The findings revealed the common types of ICTs used for the dissemination of flood risk information as Radio, Television, SMS and Social Media. The most preferred medium for weather and fishing advisory services was Television. However, for flood risk advisory service the fishermen indicates that the most preferred ICTs are the Social Media, followed by SMS. Majority believes that the weather and flood risks reduction Advisory service has lifted their self-efficacy to moderate level and hence motivation to be prepared. The research was able to determine preferred ICTs medium for specific tasks for weather, fishing and flood risks reduction advisory services. It also determine the influence on perceived self-efficacy and therefore recommended that in designing communication models and programs, the use of preferred ICTs be made while enriching the content and approach to improve the psychological state and therefore self-efficacy, attitude and motivation of the fishermen and target groups to be prepared for reduce risks of flood and weather extreme events.